2014
DOI: 10.1016/j.jadohealth.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Its Effects on Human Male Adolescent Mood and Behavior: A Systematic Review

Abstract: 23Introduction: During puberty there is an approximate twenty-fold increase in endogenous testosterone 24 in males and a more modest increase in females. This increase is often blamed for changes in mood 25 and behavior in adolescence such as aggression, an increase in risk taking and depression. The aim of 26 this systematic review is to determine what evidence exists on the effects of endogenous testosterone 27 on behavior and mood in both sexes during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 45 publications
(33 reference statements)
4
38
1
Order By: Relevance
“…The mean free and total testosterone levels of the APD group were found to be higher than those of the control group. The testosterone-aggression relationship has been investigated and demonstrated by numerous studies (17). Aggressiveness increases with the use of testosterone analogs.…”
Section: Discussionmentioning
confidence: 99%
“…The mean free and total testosterone levels of the APD group were found to be higher than those of the control group. The testosterone-aggression relationship has been investigated and demonstrated by numerous studies (17). Aggressiveness increases with the use of testosterone analogs.…”
Section: Discussionmentioning
confidence: 99%
“…This tendency to believe that violence among men is inherent has caused many to suggest that biology – especially testosterone – underlies this sex disparity in violent behavior (Batrinos, 2012; Terburg et al, 2009; Book, 2001; Nelson & Chiavegatto, 2001). This has, however, been challenged as a principle cause of aggression and violence (Duke et al, 2014; Fausto-Sterling, 1985; Lorber, 1994). Further, many argue that hormone production (including testosterone) interacts with social experiences and therefore is not a solely biological mechanism (Karkazis et al, 2012; Schulz et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is proposed to be a sensitive period for sex steroid-induced brain maturation (Cunningham et al, 2007;Koolschijn et al, 2014;Peper and Dahl, 2013;Peper et al, 2015). In adolescents, lower levels of testosterone have been associated with the presence of anxious and depressive symptoms (Granger et al, 2003, but see Duke et al, 2014). It has been suggested that sex steroid levels in combination with environmental stress and neurotic temperament constitute a vulnerability factor for the onset of mood disorders during adolescence (Mueller, et al, 2014;Silk et al, 2012;Zinbarg et al, 2016).…”
mentioning
confidence: 99%